Philosophical Education as a Tool for Individual and National Development - Idowu, Oladele Daniel (NIU Journal of Humanities; Vol 4 No 3 (2019): KIU Journal of Humanities, Vol. 4 No. 3, September 2019, 2019)
Africans have been exposed to formal education since the expansionistsâ€™ decision to colonize their territory and rule them either directly or indirectly. Education was necessary for effective communication, especially, to make the colonized do the colonizerâ€™s bidding. This type of education probably informed Frantz Fanonâ€™s description of the African as â€œBlack Skin, White Masksâ€. Even after over five decades of the independence of most African countries, the goal of education in most of these countries seem to still be in line with that of the colonizers even though there are bold statements on paper in terms of their philosophies of education. Definitely, Africans have tried as much as their counterparts from other parts of the world to master nature in order to subdue it. However, they have not done enough to understand themselves enough to be able to dominate nature. This is a gap that must be filled. Filling the above identified gap requires the philosophical sermon â€˜Man, know thyselfâ€™. The African needs to know who he is to be able to identify how to adapt available theories to his situation as well as seek new ways of addressing his peculiar needs.  This paper argues that philosophical education- education that transcends formal, science and technology based education- is necessary for individual and national development. It is our view that unless Africans imbibe the Socratic dictum and use it to wonder about themselves and everything that surrounds them, efforts at developing both the individual and the state would continue to yield little results.